(untitled) (Biological Sciences - PJSIR, 1999)
This studywascarriedouttodemonstratetheeffectofblackpointonthechangesofbiochemicalconstituents inwheatseed at different levels of manuring. Starch and total soluble carbohydrates of wheat decreased, while prolamin, glutelin and phenolics increased with the change of manuring schedule levels but method of urea application had no effect on carbohydrate and showed a tendency towards increase in total phenol and prolamin. On the other hand, glutelin and orthohydroxyphenol contentshoweddecreasingtendencyundersimilarconditions. Nitrogenalone,orincombination with cowdung,increasedthenumberofinfectedwheatseeds;itwasalsotrueformethodsofN application.Blackpointpathogens decreased starch,solublecarbohydrates andincreasedphenolics,prolaminandglutelincontentininfectedwheatseed.Due to infection marked fluctuation was observed in thecontents of reducing sugar, total phenol and prolamin of the seed.